Experimental Study on the Shear Properties of Soil around Piles with Permeation Grouting - Guisen Wang; Baoning Hong; Xin Liu; Dongning Sun; Zhiwei Shao; Yunlong Yao (Applied Sciences, 2023)
While post-grouting is frequently reported to improve the engineering performance of piles, the shear strength of the soil around piles is not well understood. To investigate the strengthening mechanism of soil around piles with permeation grouting, laboratory tests were carried out on homemade cement soil from the aspects of shear strength and microstructure characteristics. The evolution rule of the shear stress–shear displacement curve of grouting soil with different cement contents was analyzed, and the influence of grouting parameters on shear strength was explained. A composite exponential model describing the shear stress and shear displacement of permeation grouting silty clay was established. Furthermore, the influence of different cement content on changes in the microstructural characteristic parameters of the soil around piles was studied. The results show that penetration grouting has a positive effect on improving the shear strength of the soil around piles, and the failure mode of silty clay changed from elastic–plastic failure to brittle failure after grouting. Permeation grouting makes the particle structure denser, which limits the changes in pore arrangement and distribution. The shear failure of the soil around piles under permeation grouting obeys the Mohr–Coulomb criterion of failure. It is recommended to increase the grout diffusion radius during construction, considering the reinforcement effect of permeation grouting on the soil around piles.